2020
DOI: 10.3390/en13040859
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency of a Solar Wall with Transparent Insulation in Polish Climatic Conditions

Abstract: A numerical model of a solar wall (SW) with transparent insulation (TI) is proposed in this article. The model is based on the finite-difference method and thermal conductivity equation, with a heat source term for the absorber. Using this model, the energy efficiency of a solar wall with transparent insulation (SW-TI) with honeycomb insulation made of modified cellulose acetate was analyzed in the case of different climatic conditions prevailing in Poland, different orientations of the envelope, and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Using the analogy of [39], it follows that the ray trajectory can be computed by solving six coupled first-order differential equations for the components of v and r according to Equation (20).…”
Section: Short-wave Radiation Transport Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the analogy of [39], it follows that the ray trajectory can be computed by solving six coupled first-order differential equations for the components of v and r according to Equation (20).…”
Section: Short-wave Radiation Transport Modelingmentioning
confidence: 99%
“…Swirska-Perkowska et al [20] performed numerical simulations for an entire wall structure including a TIM. The introduced numerical model, which is developed for a honeycomb-type TIM made of modified cellulose acetate on a multi-layer wall, was used to predict monthly energy savings for different climatic conditions in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Without chemical admixtures, they generally have low thermal conductivity [6]. They are very popular in the construction industry [7,8], and because they can also be transparent, they are used to achieve high thermal yields, in buildings with walls with so-called high optical efficiency [9]. Mention should also be made of the so-called solar energy market, where plastics are increasingly competing with glass or metal structural elements in various solar devices due to their relatively low weight and high durability.…”
Section: Introductionmentioning
confidence: 99%
“…By using a 300 mm thick brick wall behind the TI system, summer overheating problems were reduced and delayed by up to 12 h in the office zones. An entire wall structure consisting of an internally plastered sand-lime brick and a TI system was numerically investigated in [16] from September to May for different facade orientations. It was concluded that the application of transparent insulation to a wall with an eastern or western orientation leads to a reduction of the annual effective heat gains of the building envelope in the range of 24% to 31% with respect to the value of these effective heat gains for a south-oriented wall structure.…”
Section: Introductionmentioning
confidence: 99%